Contribution of Social Forestry to Carbon Stock Reserves through Land Cover Change Analysis in the Forest Management Unit Area I NTB - Maulana, Bangkit; Sjah, Taslim; Hayati, Hayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Social forestry is one of the policy instruments expected to maintain forest carbon stock while supporting the achievement of Indonesia's climate change mitigation targets. This study aims to analyse the dynamics of carbon stock in social forestry areas within the Forest Management Unit (KPH) Region I of West Nusa Tenggara and to evaluate the difference in carbon stock before and after permit issuance. A before-after approach was applied to 45 Forest Farmer Groups, using the year of decree issuance as the reference point over a span of five years before to five years after issuance. Carbon stock was estimated by multiplying the area of each land cover class by its carbon factor, and the difference between periods was tested using the Wilcoxon Signed Rank Test. The results show that the total carbon stock of the area declined from 1,594,074 tons C to 1,038,944 tons C, a reduction of 555,130 tons C equivalent to 2,035,475 tons of CO2-equivalent. As many as 37 of the 45 groups experienced a decline, and the statistical test confirmed a significant difference between conditions before and after permit issuance (p < 0.001). This decline was primarily caused by the conversion of forested land cover into agricultural land with lower carbon factors. These findings indicate that the issuance of social forestry permits in the study area has not succeeded in maintaining carbon stock, thus requiring strengthened post-permit governance and supervision so that social forestry can contribute positively to the Forestry and Other Land Use (FOLU) Net Sink 2030 target.